1989
DOI: 10.1111/j.1151-2916.1989.tb07677.x
|View full text |Cite
|
Sign up to set email alerts
|

Zirconia Coating on Stainless Steel Sheets from Organozirconium Compounds

Abstract: The stability and the coating characteristics of a variety of organozircon i u m c o m p o u n d s h a v e b e e n investigated to coat ZrO, films on stainless steel sheets for the improvement of heat resistance against oxidation. Zirconium tetraoctylate and zirconium tetrakis(acety1acetonate) were found to be more stable than zirconium alkoxides in an ambient atmosphere. The ZrO, films from zirconium alkoxides became white and discontinuous when the thicknes? of the films exceeded about 200 A (20 nm). On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
5

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(58 citation statements)
references
References 8 publications
3
50
0
5
Order By: Relevance
“…TABLA Por otro lado, al evaluar la influencia de la composición deben diferenciarse dos variables: el efecto de la modificación en la proporción Zr/Si y el carácter híbrido de las capas, que aumenta con el contenido de MTES. Ambos efectos contribuyen de manera similar, ya que cuando se incrementa el contenido de MTES, la estructura disminuye su rigidez (debido a una menor proporción de ZrO 2 ) y aumenta la flexibilidad y carácter híbrido de la capa por el aumento de CH 3 .…”
Section: [4]unclassified
See 1 more Smart Citation
“…TABLA Por otro lado, al evaluar la influencia de la composición deben diferenciarse dos variables: el efecto de la modificación en la proporción Zr/Si y el carácter híbrido de las capas, que aumenta con el contenido de MTES. Ambos efectos contribuyen de manera similar, ya que cuando se incrementa el contenido de MTES, la estructura disminuye su rigidez (debido a una menor proporción de ZrO 2 ) y aumenta la flexibilidad y carácter híbrido de la capa por el aumento de CH 3 .…”
Section: [4]unclassified
“…La formación de defectos que permitan el contacto de áreas reducidas del sustrato con el electrolito aumenta la susceptibilidad a las picaduras, incluso respecto a la del metal desnudo. La incorporación de ZrO 2 a los recubrimientos de SiO 2 debería permitir aumentar la resistencia a medios básicos, eliminando esta situación (3). Sin embargo, para que dicho efecto sea realmente beneficioso, debe obtenerse una red homogénea, sin separaciones de fase ni segregaciones.…”
Section: Introduccionunclassified
“…Other studies on resistance to oxidation are those on ZrO 2 and ZrO 2 -Y 2 O 3 coatings (Izumi 1989;Miyazawa 1995), on CeO 2 -TiO 2 coatings , on Al 2 O 3 coatings (Özer 1999) and on silica films through salt fog tests (Kato 1992;1993). Kato found that the corrosion resistance depended on the structure of the SiO 2 coating and is enhanced by repeating the coating cycle and the temperature of the heat treatment.…”
Section: Inorganic Coatings On Different Substratesmentioning
confidence: 99%
“…In general, it can be considered that the coating behaviour is conditioned by thickness (Kato 1992;Izumi 1989), although other parameters also have an influence such as the medium of attack, the sintering temperature and the conditions for processing the coating. An important conclusion is the power of protection of these coatings against oxidation or nitridation in anhydrous media, but also the sensitivity to corrosion in electrolytic media caused by the presence of micro-cracks or defects in the coating.…”
Section: Inorganic Coatings On Different Substratesmentioning
confidence: 99%
“…Mediante la utilización del proceso sol-gel, se pueden conseguir capas densas, sin defectos y resistentes al rayado [2,3]. Este método no es muy costoso, es fácil de aplicar y posee la gran ventaja de permitir la sinterización a temperaturas tan bajas como 500ºC [4].…”
Section: Introductionunclassified